(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
A field study was conducted over two growing seasons (2022–2023 and 2023–2024) in an agricultural field in Asdira Al-Sufla area, Al-Shirqat District, northern Iraq, on bread wheat (Triticum aestivum L.). The experiment included three factors: The first factor was irrigation method at three levels (center pivot sprinkler irrigation, solid-set sprinkler irrigation, and surface irrigation).